2020
DOI: 10.1016/j.polymer.2020.122277
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic parameters guiding the localization of regioselectively modified kaolin platelets into a PS/PA6 co-continuous blend

Abstract: This article highlights the role of kinetic and thermodynamic parameters on the localization of modified kaolin platelets into a high interfacial tension co-continuous PS/PA6 blend after extrusion, injection molding and annealing. Three kinds of copolymers were synthesized and grafted on kaolin: poly(styrene-co-(methacryloyloxy)methyl phosphonic acid) copolymer (P(S-co-MAPC 1 (OH) 2)), polystyrene terminated 3-(mercaptopropyl)triethoxysilane, (ETS-PS) and poly (styrene-co-3-methacryloxypropyltrimethoxysilane) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Previous research found that in compatible blends, the cocontinuous morphology is formed by fiber−fiber linkages, while in the incompatible blends, the elongated threads break easily and thus form the droplet morphology. 26,27 The dispersed phase of compatible blends is more likely to form into a fibrous morphology during processing than incompatible blends. As seen in Figure 3a, stress transfer from the matrix to the dispersed phase is difficult because of the weak interaction between the two phases, which is certified by the pulled-out PA6 phase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that in compatible blends, the cocontinuous morphology is formed by fiber−fiber linkages, while in the incompatible blends, the elongated threads break easily and thus form the droplet morphology. 26,27 The dispersed phase of compatible blends is more likely to form into a fibrous morphology during processing than incompatible blends. As seen in Figure 3a, stress transfer from the matrix to the dispersed phase is difficult because of the weak interaction between the two phases, which is certified by the pulled-out PA6 phase.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research on blends compatibilized by nonofillers mainly focused on particle location and its effects on the blend morphology, but the migration process of particles during blending remains unclear. Taguet et al compatibilized PS/PA6 blends by kaolin platelets, and found that kaolin platelets would migrate from the PA6 phase to the blend interface during dynamic annealing, thus limiting the coalescence of the dispersed phase. Göldel et al studied the migration of multiwalled carbon nanotubes in polymer blends.…”
Section: Introductionmentioning
confidence: 99%
“…Nitric acid solution (HNO 3 , 68% w/w) was supplied by Prolabo (Paris, France), and gallic acid powder with purity of 98% was purchased from Acros Organics, Geel, Belgium. Silane grafting agents (Figure 1) trimethoxyoctadecylsilane (named Si-C18) and 3-aminopropyletriethoxysilane (named Si-NH 2 ) were purchased from ABCR (Lyon, France), while poly(methylmethacrylate-co-3-(triethoxysilyl)propyl methacrylate) 95/5% mol noted Si-PMMA and poly(styrene-co-3-(triethoxysilyl)propyl methacrylate) 95/5% mol noted Si-PS were synthesized in the laboratory using a protocol detailed in a previous study [64]. Polymethylmethacrylate (PMMA) Altuglas V825T was purchased from Arkema (Milan, Italy), and polyamide (PA6) Ultramid B33 was purchased from BASF (Ludwigshafen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…12 It is essential to selectively localize nanofillers in the governance of the blends' morphology. 13 The co-continuous morphology have been mediated with a large number of nanofillers, including silica, 14,15 nanoclay, 16,17 cellulose nanocrystal, 18 and synthetic nanorods, 5,19,20 etc. Specially, Janus particles, combining the amphiphilicity of a compatibilizer and the Pickering effect of a nanoparticle, 21,22 could impact the blends' morphology through a multiple viscoelasticity mechanism.…”
Section: Introductionmentioning
confidence: 99%